The influence of inflation towards unemployment in Indonesia - Siska Angriani Hasibuan (Proceedings of AICS - Social Sciences, 2017)
The purpose of this research is to know the level of significance of inflation against unemployment in Indonesia year of 2003-2015. This study used a Simple Linear regression analysis method. The research results reveal that the value of F is 1.771. The conclusions of these studies mentions that variable inflation do not have significant influence of unemployment in theory Curve Phillips as indicated by higher levels of probability values are compared with the the level of significance (α = 0.05). In addition , the impact of which is demonstrated by the dependent variables independent of the variable indicated by the value of R2 at the rate of 0.372 representing 37.2%, 62.9% leaving from the impact is affected by external factors of this research.